A PRIMAL view of the Milky Way, made possible by Gaia and M2M modelling. Issue 67 (17th July 2015) - Hunt, J.A.S.; Kawata, D.
Abstract : We have developed our original made-to-measure (M2M) algorithm, primal, with the aim of modelling the Galactic disc from upcoming Gaia data. From a Milky Way like N -body disc galaxy simulation, we have created mock Gaia data using M0III stars as tracers, taking into account extinction and the expected Gaia errors. Inprimal, observables calculated from the N -body model are compared with the target stars, at the position of the target stars. Usingprimal, the masses of the N -body model particles are changed to reproduce the target mock data, and the gravitational potential is automatically adjusted by the changing mass of the model particles. We have also adopted a new resampling scheme for the model particles to keep the mass resolution of the N -body model relatively constant. We have appliedprimal to this mock Gaia data and we show thatprimal can recover the structure and kinematics of a Milky Way like barred spiral disc, along with the apparent bar structure and pattern speed of the bar despite the galactic extinction and the observational errors.